Maternal-Fetal Attachment (MFA) in the Context of Pregnancy Adaptation: A Literature Review of Internal and External Factors Affecting Mothers - Umi Aniroh; Tina Mawardika (Health & Medical Sciences, 2026)
This study aims to analyze Maternal Fetal Attachment (MFA) within the context of pregnancy adaptation by examining the influence of internal and external maternal factors through a qualitative descriptive literature approach. The research employs a library study method using secondary data sources, including peer reviewed journal articles and relevant academic documents, collected through systematic literature search and analyzed using thematic analysis, data reduction, categorization, and inductive interpretation. The findings reveal that MFA is a multidimensional construct influenced by internal factors such as maternal mental health, particularly depression and anxiety, as well as positive psychological states, and external factors including social and family support. Pregnancy adaptation emerges as a key mediating process that connects these factors to the quality of maternal fetal bonding. The study also highlights that strong MFA contributes to positive infant developmental outcomes, especially in emotional regulation and adaptive behavior. These findings imply that maternal well being and supportive social environments are essential components in strengthening prenatal attachment. In conclusion, this study contributes to the theoretical understanding of MFA as a biopsychosocial process and provides practical insights for integrating mental health screening and family centered interventions in antenatal care to improve maternal and child health outcomes.